In the Circle of White Stones : Moving through Seasons with Nomads of Eastern Tibet - Tan, Gillian G.; Tan, Gillian G. (Book collections on Project MUSE., 2017)
"In this ethnographic narrative of subsistence on the Tibetan plateau, anthropologist Gillian Tan describes the life-worlds of Tibetan nomads in a region traditionally known as Kham. The people of Dora Karmo (Circle of White Stones) are pastoralists who move with their yaks from pasture to pasture and depend on the milk production of their herd for sustenance. Tan's story, based her on own experience of living through seasonal cycles with the people of Dora Karmo between 2006 and 2013, examines the community's powerful relationship with a Buddhist lama and their interactions with external agents of change. As Buddhists, they believe in the never-ending cycle of life and death through reincarnation. Death, then, is not regarded as permanent loss but as the opportunity for continual change. Portrayals of personal loss through natural causes and revenge feuds, as well as sky burials, illustrate how impermanence permeates daily life. These pastoralists have adapted since 1959 to conditions imposed by the Chinese state through a combination of acquiescence, strategy, and resistance. They have also started to participate in the markets of a rapidly modernizing China, and in projects of international development that originate outside their own belief systems and social structures. In showing how the people of Dora Karmo perceive their environment and dwell in their world, Tan calls on development agents to consider this different worldview before they initiate projects among and for nomads"...Provided by publisher.